PENGARUH PROFITABILITAS, ARUS KAS OPERASI, DAN ARUS KAS BEBAS TERHADAP DIVIDEN KAS PERUSAHAAN DI BURSA EFEK INDONESIA - HUda, Samsul (Jurnal Ilmu Manajemen, 2018)
This research aims: (1) to find impact of profitability, operating cash flows,free cash flows simultaneously to cash devidend at Manufacture Companiesof Raw and Chemical Industry in Indonesian Stock Exchange, and (2) to findimpact of profitability, operating cash flows, free cash flows partially to cashdevidend at Manufacture Companies of Raw and Chemical Industry inIndonesian Stock Exchange.Design used in this research is associative. Analysis method used qualitativeand quantitative method. Variables used are four variables, those areindependent variables which Profitability (X1), Operating Cash Flows (X2),and Free Cash Flows (X3), and also dependent variables is Cash Dividend(Y). Population in this research as much 66 companies. Sample used asmuch 58 companies. The analytical tool used is multiple linear regression.According to the research result, find: (1) Profitability, operating cash flows,and free cash flows simultaneously have positive and significant effects tocash devidend at Manufacture Companies of Raw and Chemical Industry inIndonesian Stock Exchange and (2) Profitability, operating cash flows, andfree cash flows partially have positive and significant effects to cashdevidend at Manufacture Companies of Raw and Chemical Industry inIndonesian Stock Exchange.